Intrarenal Doppler approaches in hemodynamics: A major application in critical care - Qian, Xiaoling; Zhen, Junhai; Meng, Qingxiang; Li, Li; Yan, Jing (Frontiers in Physiology, 2022)
The treatment of severe patients generally requires increased multimodality hemodynamic monitoring, particularly of tissue and organ perfusion tracking. However, at the bedside, renal perfusion status is still inadequately investigated. Besides, in a severe patient, ultrasound is increasingly utilized to guide hemodynamic management, and Intrarenal Doppler (IRD) is increasingly used to assess renal perfusion from both the intrarenal artery and vein perspectives. The renal resistive index (RRI), which reflects the renal arterial blood flow profile, has been used to predict the reversibility of renal dysfunction and to titrate hemodynamic support. Intrarenal venous flow (IRVF) patterns, along with the renal venous stasis index (RVSI) indicating intrarenal vein blood flow profile, have been a novel tool for assessing intravenous congestion and may be useful in not only predicting an increased risk of acute kidney injury but also in fluid management by avoiding fluid overload. IRD provides diverse and supplemental information about renal perfusion and may be useful in the hemodynamic management of early diagnosis, treatment, and prognosis in severe patients. This review focuses on the specific operational methods, influencing factors, and applications of IRD in hemodynamics.